Improving Delivery Behaviors During Exposure Therapy: A Cluster Randomized Controlled Training Trial with Community Therapists. Issue 2 (3rd April 2021) - Benito, Kristen G.; Herren, Jennifer; Freeman, Jennifer B.; Garcia, Abbe M.; Kemp, Joshua; Chorpita, Bruce F.; Sung, Jenna; Arora, Aishvarya; Georgiadis, Christopher; Stewart, Elyse; Wellen, Brianna; Frank, Hannah E.; et al.
ABSTRACT: This study tested whether a new training tool, the Exposure Guide (EG), improved in-session therapist behaviors that have been associated with youth outcomes in prior clinical trials of exposure therapy. Sixteen therapists in practice settings treated 46 youths with an anxiety disorder or obsessive-compulsive disorder (OCD). Therapists were randomly assigned to receive "gold-standard" exposure therapy training with weekly consultation (GS) or "gold-standard" training with weekly consultation plus the EG (EG). The primary outcome was therapist behavior during in-session exposures, observed using a validated coding system. Secondary outcomes included training feasibility/acceptability and observer-rated patient fear habituation; we also explored independent evaluator-rated clinical outcome. As hypothesized, therapists used similarly high rates of exposure with patients in both groups, but those in the EG condition used more fear-increasing behaviors and fewer fear-decreasing behaviors compared with those in the GS condition. Attendance data and therapist feedback support EG feasibility and acceptability. Patients treated by EG-trained therapists showed increased rates of in-session habituation. Descriptive clinical outcome data showed a slightly higher treatment response rate in the EG group (66.7% EG, 58.8% GS) that was more pronounced among patients completing a posttreatment assessment (83.3% EG, 60.0% GS). Results confirm the effectiveness of EG training for improving therapist delivery behaviors. Future studies will be needed to determine whether EG training can improve rates of patient treatment response via improved delivery behaviors. Public Health Significance : This study shows that the Exposure Guide, a therapist training tool, improves therapist delivery of exposure.